Digital Manufacturing Tools in the Simulation of Collaborative Robots: Towards Industry 4.0 - Lima, Fábio; de Carvalho, Caroline Nogueira; Acardi, Mayara B. S.; dos Santos, Eldiane Gomes; de Miranda, Gabriel Bastos; Maia, Rodrigo Filev; Massote, Alexandre Augusto (Brazilian Journal of Operations & Production Management, 2019)
Goal: The main objective of this study is to analyze the impact of inserting a collaborative robot in a production line of a factory of the automotive sector. Design / Methodology / Approach: Two simulation environments were developed. The first one models the original operation without the collaborative robot. The second one evaluates the impact of inserting the robot. This work is quantitative. Results: The paper presents the use of digital manufacturing tools in a simulation of a collaborative operation between a human and a collaborative robot. The simulations with and without the collaborative robot were performed, and they make it possible to emphasize the benefits of the collaborative operation in a real production line. Limitations of the investigation: The first simulation scenario was validated from the real data provided by the factory. However, the second scenario is a suggestion, emphasizing the benefits of collaborative operation. Implementation of the second scenario was not conducted. Practical implications: Since its completion depended on support from the automotive sector, this work is noticeably practical. The real data used in the first scenario as well as the assumptions made in the second scenario allow one to conclude that it is possible to implement the propositions with the collaborative robot in the chosen line. Originality / Value: The use of the collaborative robot in Brazil was forbidden by regulation until recently. Even in other countries decision makers still find have difficulty deciding for this new technology. For this reason, the benefits of using collaborative robots, mainly in Brazilian companies, is still not clear. This work contributes to the collaborative robot discussion and consequently to Industry 4.0 implementation by creating a digital twin of an existing process and inserting a collaborative robot in it. The results should be used by decision makers to decide for inserting this technology in their factories.